Development of Educational Administration System Based on Buddhist Principles in Thailand in the AI Era - Vādasaddho, Phraphalad Honda; Marasri, Sarinya; Thanapanyo, Phra Maha Amphon; Techathammo, Phrakhruwinaithon Worawuth; Mahahing, Prachit (Journal of Buddhist Education and Research (JBER), 2026)
This academic article aims to present approaches for developing an educational administration system based on Buddhist principles in the era of Artificial Intelligence (AI) in Thailand. The study analyzes the integration of Buddhist Dhamma with AI technology to enhance educational management quality in alignment with the Thai social context. Using documentary analysis and literature synthesis from secondary sources including the Tipiṭaka, commentaries, Buddhist texts, and relevant national and international research articles, the study found that the Four Bases of Success (Iddhipāda 4: Chanda, Viriya, Citta, Vīmaṃsā) can be integrated with AI systems in educational administration across four dimensions: (1) AI-driven strategic vision (Chanda), (2) intelligent organizational mobilization (Viriya), (3) data-driven goal commitment (Citta), and (4) continuous monitoring and improvement (Vīmaṃsā). Furthermore, the Four Sublime States (Brahmavihāra 4: Mettā, Karuṇā, Muditā, Upekkhā) serve as a critical ethical framework for governing AI use in education to ensure fairness and humaneness. The article proposes the “B-AI-Ed Model” (Buddhist-AI-Education Model) as a prototype for educational administration that balances Buddhist principles with AI technology, aiming to develop Thai education that is quality-driven, morally grounded, and modernized in the global digital context.